Fluoride Binding to Streptococcus mutans Pellets Rich in Extracellular Polysaccharides - Pagotto, Leonardo Libardi; Spinola, Manuela Da Silva [UNESP]; Nóbrega, Diego Figueiredo; Cury, Jaime Aparecido; Tenuta, Livia Maria Andaló (Karger Publishers, 2021)
Extracellular polysaccharides (EPS), mainly the insoluble ones, increase the cariogenicity of dental biofilm, but whether they interfere with the binding and retention of fluoride is unknown. EPS-rich (EPS+) and EPS-poor (EPS-) pellets of Streptococcus mutans were formed and treated with increasing fluoride concentrations (0, 0.1, 1, or 10 mM). A concentration-dependent fluoride binding was observed in both EPS-and EPS+ pellets, but the presence of EPS did not affect the retention of fluoride in the pellets. In conclusion, the data suggest that a matrix of dental biofilm rich in EPS does not affect fluoride retention in the biofilm.